Failure location effects on slow crack growth parameter estimates - Jonathan Salem; Pappu L. N. Murthy (International Journal of Ceramic Engineering & Science, 2024)
Abstract As part of Roman Space Telescope component development, the slow crack growth (SCG) parameters of a glass were measured using constant stress rate testing of ASTM C1161 beams. Failures occurred on the faces, bevels and sides of the test specimens thereby providing an opportunity to examine the effects of failure location on SCG parameter estimates. Censoring of the data by location did not have a statistically significant effect on the slow crack growth parameter estimates. Linear and nonlinear fits were also made to various strength estimators. Nonlinear fits gave slightly lower estimates of the parameters. The main influence on parameter estimates was a low strength, infrequent flaw population. Exponential model parameters were estimated via swarm optimization.